Every Uniquely Remotal Set in a Hilbert Space is aSingleton (European Journal of Pure and Applied Mathematics, 2024)
In this paper we prove that every uniquely remotal set in a Hilbert space is a singleton.
Keywords: uniquely remotal, singleton; Farthest points; Uniquely distant sets